Information-seeking Behavior of Dairy Farmers regarding Prevention of Zoonotic Disease - Ahuja, Rakesh; Gautam; Sarita; Rachna; Singh, Ruchi (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The present study was carried out to ascertain dairy farmers’ information-seeking behavior regarding the prevention of zoonotic diseases. The study was conducted in 8 villages chosen randomly from 2 districts of Haryana state. A majority of the respondents had moderate information-seeking behavior about zoonoses. This was assessed in terms of ‘sources of information’ and ‘extent and how frequently the information was sought.’ Further, the correlation between the respondents’ personality traits and their information-seeking behavior scores revealed that different variables like extension participation, social participation, caste, and risk orientation exerted significant influence. Most of the time, the sources utilized by the respondents were progressive and co-farmers, followed by veterinary hospitals, neighbors/ friends, training, etc. Respondents sought more information on selection criteria for disease-free animals, storage of feed, supplemental feed preparation, and health care. It is suggested that further studies to understand the factors affecting the information behavior of farmers are needed.